Incentive Pay and Performance: Insider Econometrics in a Multi-Unit Firm - Hein Bogaard; Jan Svejnar (Institute for the Study of Labor (IZA), 2013)
We exploit organizational reforms in a foreign-owned bank in Central-East Europe to study the implementation of modern HRM policies in an emerging market context. We have branch-level data and use our knowledge of the process that led to the adoption of the reforms to implement two estimators that address endogeneity bias in a complementary fashion: an IV approach and Generalized Propensity Score estimation. Our results show that some of the reforms had a positive impact on productivity, but they also underscore the risks of quantity-based incentives where quality is important.
Keywords: F23; G21; M52; 330; insider econometrics; endogeneity of HRM policies; incentives; foreign ownership; banking; Central and Eastern Europe